Nutritional interventions to prevent and reduce overweight and obesity during postacute stroke rehabilitation: a scoping review protocol - Dorthe Sørensen; Lena Aadal; Mette Nørtoft (BMJ Open)
Introduction Individuals with stroke are at risk of long-term overweight and obesity due to biopsychosocial factors. Being overweight and obese is associated with an increased risk of numerous chronic conditions, including recurrent stroke. Unfortunately, recommendations for nutritional interventions vary. The objective of this scoping review is to identify and map the body of literature on professional nutritional interventions aimed at preventing or reducing overweight and obesity during postacute stroke rehabilitation.Methods and analysis The review follows the Joanna Briggs Institute methodology for scoping reviews. A three-step librarian-assisted search strategy will be conducted using the bibliographic databases MEDLINE (PubMed), Embase, CINAHL and Web of Science. Indexed and grey literature in English and Scandinavian languages, from January 2010 to the present, will be considered for inclusion. The scoping review will include materials such as research articles, methodological papers and clinical guidelines that report on nutritional interventions aimed at preventing or reducing overweight and obesity among individuals with stroke (aged ≥18 years) from admission to rehabilitation hospitals. We will map and identify any kind of nutritional intervention in rehabilitation hospitals, nursing homes or their own environments in high-income countries. Two independent reviewers will conduct an iterative process for screening the identified literature, paper selection and data extraction. Disagreements will be resolved through discussion or with an additional reviewer. A data extraction form will be used to guide the data extraction.Ethics and dissemination This review will involve the collection and analysis of secondary sources that have been published and/or are publicly available. Therefore, ethical approval is not required. The results will be published in an international peer-reviewed journal, presented at scientific conferences and disseminated through digital science communication platforms.Trial registration number The protocol is registered in the Open Science Framework: https://osf.io/ga63n/view_only=ee07beace7bb48d6b9c82cbf79cf2e95.